Short Term Treatment of Shrimp Aquaculture Wastewater using Water Hyacinth (Eichhornia crassipes) - Lee, Nyanti; Berundang, G.; Ling, T. Y. (IDOSI Publications, 2010)
Among the environmental concerns of shrimp aquaculture is pollution from pond effluent. Water hyacinth was found to be effective in treating different types of wastewater. Therefore, in this study the potential of short term treatment of pond effluent was investigated. Wastewater from newly harvested shrimp pond was placed in fiberglass tanks outdoor where water surface was fully-cover (F), half-cover (H) and not covered (control) (C) with water hyacinth for 76 hours. Results show that percent reductions were in decreasing order of F>H>C in all the parameters studied. Ammonia nitrogen in F decreased from 1.8 mg/L to 0.2 mg/L in 46 hours whereas in Hand C, their concentrations were above 0.6 mg/L. For F treatment, percentage reductions ranged from 52.5 to 100010 and were in the order of N03-N>N02-N>TP>TAN>TN>TSS>RP>BODs>COD. In H, reduction ranged between 45.4 to 95.2% and in C they ranged from -18.5% to 74.9%. First order decay coefficient for all the parameters were the highest in F followed by Hand C treatments. This study showed that even though the duration of the treatment was short, suspended solids, oxygen demand, nitrogen and phosphorus reductions were significantly higher in the water hyacinth treatments compared to treatment without water hyacinth.